St. Thomas’ Baby Fund Recipe Book, with a foreword by Josceline Dimbleby - D., J.M. (Petits Propos Culinaires, 1992)
St. Thomas’ Baby Fund Recipe Book, with a foreword by Josceline Dimbleby: Sutherland Press, Golspie, Sutherland, Scotland, 1992: 144 pp: amusing b/w drawings, paperback £4.50. Obtainable at St Thomas’ Hospital, London SEl 7EH or send a check for £5.00 (to include P&P) to: Tommy, London, SE99 6RD.